Influence of all-out start duration on pulmonary oxygen uptake kinetics and high-intensity exercise performance - Wood, M. A.; Bailey, S. J.; Jones, A. M. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the influence of the duration of an "all-out" starting strategy on O2 uptake kinetics and performance during high-intensity exercise. Following familiarization, 9 recreationally active men completed three 1500-m cycling time trials (TT) using different pacing strategies. In a randomized order, subjects completed a self-paced TT (SPTT), or a TT that was self-paced following an initial 15-second (15TT) or 90-second (90TT) all-out sprint. VO2 was measured during all tests. The 1500-m TT completion time was faster in 15TT than SPTT (136.1 ± 6.2 seconds vs. 140.3 ± 7.1 seconds; p < 0.05), but 90TT (138.5 ± 8.5 seconds) was not significantly different from either SPTT or 15TT (p > 0.05). The VO2 mean response time (MRT) was shorter in 15TT (27 ± 7 seconds) and 90TT (30 ± 9 seconds) than SPTT (40 ± 10 seconds; p < 0.05), but the peak VO2 was only higher in 15TT (3.77 ± 0.42 L/min) compared with SPTT (3.47 ± 0.44 L/min) (p < 0.05). There was a significant correlation (r = 0.77, p < 0.05) between the shorter MRT and the faster 1500-m completion time for 15TT compared with SPTT. These results support the use of a brief (~15 seconds) all-out start to improve performance in short-duration (<180 seconds) athletic events and suggest that such a strategy may be ergogenic by increasing the rate of oxidative energy transfer during exercise while minimizing the extent of the concurrent muscle metabolic perturbation.